MANAJEMEN SUMBER DAYA MANUSIA - Yudi Ardian Rahman (Tsaqofah: Jurnal Pendidikan Islam, 2020)
In the Islamic perspective, education has played an important role in the effort to give birth to humans who are reliable and can answer the challenges of the times. Human Resources (HR) has a central position in realizing development performance, which places humans in their function as development resources. Human resources play a role in determining a country's progress. The existence of the Indonesian nation in the midst of the current global era, will be influenced by the ability of Indonesian human resources, especially those characterized by the ability to master science and technology and the establishment of faith and taqwa to the Supreme God. One of the most important resources in management is human resources.